Is three a crowd or a coalition? : India, Brazil and South Africa in the WTO - Du Preez, Mari-Lise (Stellenbosch : University of Stellenbosch, 2007)
Thesis MA (Political Science. International Studies))--University of Stellenbosch, 2007.